2015
DOI: 10.1007/s11356-015-4648-7
|View full text |Cite
|
Sign up to set email alerts
|

National monitoring of nicotine use in Czech and Slovak Republic based on wastewater analysis

Abstract: The aim of this study was to compare estimation of nicotine use in Slovakia (SR) and the Czech Republic (CR) based on cotinine analysis in wastewater from seven selected wastewater treatment plants (WWTPs) with conventional estimation based on tobacco product sales. Urinary bio-markers of nicotine use were analyzed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). The study was performed concurrently at all the WWTPs (from 11 to 18 March 2014). Representative 24 h composite samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…In addition, a large amount of dipping tobacco is disposed of into urinals and toilets resulting in increased nicotine residues in Oslo´s wastewater influent. Cigarette consumption may vary greatly within countries [ 40 ] and other studies have shown a better agreement when comparing WBE with smoking prevalence data at regional level [ 6 , 7 , 29 , 52 ]. Nicotine metabolites have been proposed and used as quantitative biomarkers to estimate population size at local level [ 7 ] although the presented results and previous studies [ 53 ] demonstrate that the different tobacco culture-dependent and geographic behaviour may change between countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a large amount of dipping tobacco is disposed of into urinals and toilets resulting in increased nicotine residues in Oslo´s wastewater influent. Cigarette consumption may vary greatly within countries [ 40 ] and other studies have shown a better agreement when comparing WBE with smoking prevalence data at regional level [ 6 , 7 , 29 , 52 ]. Nicotine metabolites have been proposed and used as quantitative biomarkers to estimate population size at local level [ 7 ] although the presented results and previous studies [ 53 ] demonstrate that the different tobacco culture-dependent and geographic behaviour may change between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine absorption was estimated and cigarette consumption calculated based on the average absorption of nicotine from tobacco cigarettes . The approach has now been applied in Belgium, China, Czech and Slovak Republics, Portugal and Spain . Publications to date have concentrated mainly on European communities.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, survey methods and sales data have been used to monitor tobacco and alcohol consumption but recently wastewater analysis or wastewater‐based epidemiology (WBE) has been used as an alternative method to estimate the consumption of chemicals at the population level . There are already some WBE studies that have monitored the consumption of alcohol and tobacco in different populations, from multiple cities to music festivals . These studies were based on the measurement of the unique metabolites of ethanol, ethyl sulfate (EtS), and ethyl glucuronide (EtG), and the metabolites of nicotine, cotinine (Cot), and trans‐3′‐hydroxycotinine (HCot).…”
Section: Introductionmentioning
confidence: 99%
“…3 There are already some WBE studies that have monitored the consumption of alcohol and tobacco in different populations, from multiple cities to music festivals. [4][5][6][7] These studies were based on the measurement of the unique metabolites of ethanol, ethyl sulfate (EtS), and ethyl glucuronide (EtG), and the metabolites of nicotine, cotinine (Cot), and trans-3′-hydroxycotinine (HCot). In WBE, the use of metabolites like EtG, EtS, Cot, and HCot ( Figure 1) as biomarkers are preferable to the use of parent compounds, because it avoids the uncertainty caused by the potential direct disposal of alcohol and tobacco, cigarette stubs, or nicotine products into the sewer.…”
mentioning
confidence: 99%